Challenges and Opportunities in Clinical Ethics with the Implementation of Korea’s End-of-Life Act - Junga Kim, Claire (Acta Bioethica, 2019)
This paper examines the possible impacts of the Act on Decisions on Life-Sustaining Treatment for Patients in Hospice and Palliative Care or at the End of Life in Korea (Korea’s end-of-life act), legislated in 2016, on the development of hospital ethics committees and clinical ethics consultation services in South Korea. Clinical ethics in Korea has not made much progress in comparison to other subdisciplines of biomedical ethics. While the enactment of this law may give rise to beneficial clinical ethics services, it is possible that customary practices and traditional authorities in Korean society will come into conflict with the norms of clinical ethics. This paper examines how the three main agents of Korean society—family, government, and medical professionals—may clash with end-of-life stage norms in clinical ethics, thus posing obstacles to the development of hospital committees and consultation services. A brief outline of what lies ahead for the progress of clinical ethics practice is explored.